Applying linear mixed model to farm panel data set - Sinisalo, Alina (Statistics Estonia, 2014)
The development of production costs were studied in Finnish farms in 2000- 2011 with a linear mixed model taking into account farm-level information (production type, economic size, arable land) and time effect. Interindividual differences in intraindividual changes over time were analyzed. The production cost increased over time and as the size of arable land and standard output increased.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; linear mixed model; panel data; Suomi; maatilat; kustannukset; farms; costs; Finland; linear models; lineaariset mallit